Fetal safety of levetiracetam use during pregnancy - Koc, Guray; Guler, Selda Keskin; Karadas, Omer; Yoldas, Tahir; Gokcil, Zeki (Springer Heidelberg, 2018)
The aim of this study is to evaluate the effect of levetiracetam treatment during pregnancy on fetus.. The pregnant women with epilepsy (PWWE) who were exposed to levetiracetam treatment during pregnancy in the form of monotherapy or polytherapy were retrospectively evaluated. They were compared with the PWWE who did not use the antiepileptic drug (AED) during pregnancy. A total of 102 pregnancies were examined. While 35 patients never used AED during pregnancy, 30 patients received only levetiracetam therapy, and 37 patients received levetiracetam with at least one combined AED. While no major congenital malformation (MCM) was determined in the group of patients who never used AED and who received levetiracetam monotherapy, 2 MCMs were determined in the group receiving multiple AED therapy with levetiracetam. This study showed that the use of levetiracetam as monotherapy during pregnancy was at the same risk level as the group who never used AED and that the risk increased when it was used as a part of polytherapy. In conclusion, these findings support the current understanding that LEV may be a feasible option for PWWE.
Keywords: Pregnant woman with epilepsy; Levetiracetam; Major congenital malformation; Monotherapy; Seizures